HIV/AIDS in the Middle East and North Africa : the costs of inaction - Jenkins, Carol Lynn (Orientations in development., 2003)
This work shows that although most evidence suggests HIV prevalence is low in the Middle East and North Africa region, greater investments in improved surveillance, prevention, and care are needed - to maintain low prevalence levels and preserve the focus on national and regional development goals.